Political positioning and local issue salience in the digital age: Evidence from regional elections in an archipelagic province - Fadli, Kasirul; Johannes, Johannes; Rosita, Sry; Dahmiri, Dahmiri (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
This study analyses the influence of political positioning on voter preferences, with local political issues functioning as a mediating variable within the framework of digital political marketing. Using a quantitative explanatory survey design, data were collected from 349 eligible voters in the Riau Archipelago Province and examined using Partial Least Squares Structural Equation Modeling (SEM–PLS) via WarpPLS 8.0. The results show that political positioning significantly affects voter preferences and that the salience of local political issues partially mediates this relationship. These findings highlight that positioning strategies are more effective when aligned with context-specific issues in geographically fragmented regions, thereby strengthening both emotional and cognitive voter evaluations. Theoretically, the study advances digital political marketing and issue-based voting frameworks, and, practically, offers guidance for designing contextually relevant political narratives in archipelagic settings.